Parents' Weekend dance class in Jackson Gym and drama performance in the Balch Arena Theatre. Photo 073 - Tzanev, Zara (Tufts Archival Research Center, 2008)
Parents' Weekend dance class in Jackson Gym and drama performance in the Balch Arena Theatre.